Microstructure and mechanical properties of a bulk ultrafine grained Al-7Si-0.3Mg alloy produced by thermomechanical consolidation of a nanocrystalline powder - Liang, J.; Kong, C.; Quadir, Md Zakaria; Zheng, Y.; Yao, X.; Munroe, P.; Zhang, D. (Elsevier S.A., 2016)
A nanocrystalline Al-7Si-0.3Mg (wt%) alloy powder prepared by high energy mechanical milling was consolidated by two powder metallurgy routes to produce a bulk ultrafine grained Al-7Si-0.3Mg Alloy: vacuum hot pressing (VHP) in combination with hot extrusion (HE) and spark plasma sintering (SPS) in combination with HE. Dynamic recrystallization, Al grain growth, Si particle coarsening and formation of GP zones occurred during consolidation. Meanwhile, with increasing the extrusion ratio, the Si particles distribution became more uniform due to the flow of Si particles. With the VHP-HE route, increasing the extrusion ratio from 9:1 to 25:1 improved the tensile strength by 7.8% and elongation to fracture by 51% due to decrease of average grain size, enhancement of interparticle bonding and more uniform Si particle distribution. Similarly, with the same extrusion ratio of 9:1, the use of SPS instead of VHP for the first consolidation step did not change the tensile strength significantly, but improved the elongation to fracture by 90% for the same reasons. Analysis of the various contribution mechanisms to the yield strength shows that grain boundary strengthening and GP zone strengthening make the major contributions.